Digital Accounting Teaching Materials In Practical Services, Trade And Manufacturing - Aprillia Aprillia (Universitas Internasional Batam, 2021)
The spread of the COVID-19 epidemic in the world has prompted the Indonesian Government to immediately take the initiative to impose activity restrictions to suppress the quantitative growth in the number of victims. Thus, the closure of educational institutions, which resulted in remote distance and online learning is also necessary. Considering the sudden implementation, struggle among students and teachers during the study period is inevitable. One of the most common obstacles that is found in the practice is due to the underdeveloped study materials. Therefore, in order to fill in the flaw in the current circumstances, this article aims to compile interesting digital accounting teaching materials on practical services, trade and manufacturing in the form of modules, powerpoints, and videos. The material compiled below, is based on the interview, observations, documentation and simulations conducted by the author in local Vocational High School. The implementation results of this activity are being compiled into modules which contain material, powerpoints and videos which have been carefully refined into compact and understandable materials without overlooking the completeness of the subject coverage. The author recommendation for the researcher or observant who is interested in the same research is to include quizzes and interactive questions to improve student motivation and interaction during the class.